VIVÊNCIAS COTIDIANAS DO CUIDADOR FAMILIAR DE IDOSOS SUBMETIDOS À HEMODIÁLISE - MUNIZ, Renata Suenne Costa de Sousa (2018)
The meanings attributed to chronic diseases are not only the domain of the sick individual, butalso of their relatives, who need to reorganize in order to provide the necessary support to thepatient during the treatment. When the patient is an elderly person, multiple factors are added to his or her illness, which results in the family caregiver being at a loss as the family takes ona new role, to the detriment of their personal aspirations, plans, expectations and daily routine.In this context, the objective of the study is to investigate, know and describe the daily experiences of family caregivers of elderly people with chronic kidney disease undergoing hemodialysis in a university hospital. The theoretical approach given to the object of study is based on the Psychology of Health considering the psychosocial impacts generated by the process of illness and treatment of chronic diseases, such as kidney disease. The study was conducted according to the qualitative methodology in the nephrology department of the University Hospital of the Federal University of Maranhão, Presidente Dutra unit, São Luís - MA. A sociodemographic questionnaire and a semistructured interview script were used for the data collection during the period of June and July of 2018. The results had a sample of eight family caregivers, predominantly male, married, with a complete secondary education and, in its scope, in an unemployment situation. Caregivers have brought financial difficulty asthe main change in taking care of the elderly, coupled with the scarcity of time available for self-care, rest, leisure, social, family and emotional life. They reported that immersion in the role of caregiver occurred automatically, as an act of reciprocity of care and a matter of moral obligation. They attributed the lack of orientation about the disease and treatment, the main difficulty faced when assuming the role of family caregiver of the elderly, added to the unavailability of other relatives, contributing to the high level of overload and anxiety experienced in their daily lives. The study evidenced the need and importance of the support and reception of the health team to the family caregiver, stimulating their search for informationand guiding them to deal with the care situation and their demands. The data from this study are limited to a local reality, requiring further research to foster the particularities and difficultiesfaced by caregivers.